On the Issue of Determining Parameters in Models and Criteria of Dynamic Spallation Fracture. (2017) - Volkov, I.A.; Igumnov, L.A.; Ipatov, A.A.; Vorobtsov, I.V.
Abstract: The issue of determining material parameters and scalar functions in models and criteria of dynamic spallation fracture is discussed. An experimental-theoretical methodology to obtain them for the dynamics of failing elastoplastic media is presented, which consists in analyzing inverse problems. The methodology involves testing specimens of the studied material, using special regimes of dynamic loading, followed by analyzing a number of numerical modeling problems. For models and criteria of dynamic spallation fracture, the methodology is based on minimizing the quadratic deviation between experimental and analytical data containing information on the kinetics of the spallation fracture process. The reliability and unambiguity of the determined material parameters is demonstrated by comparing the experimental and analytical data.